THE EFFECT OF PRODUCT QUALITY AND PRICE PERCEPTION ON CUSTOMER SATISFACTION ON SOMETHINC PRODUCTS - Bani Zamzami (Asosiasi Dosen Muda Indonesia, 2022)
This study used primary data and the method of data collection was done through distributing questionnaires to 100 respondents. The data collection technique used is probability sampling with a simple random sampling method. In this study, the sample taken is all consumers in Indonesia who buy and use SomeThinc products. To find out between variables, the authors use analytical tools such as Likert scale, validity test, reliability test, classical assumption test, multiple linear regression analysis, F test, T test and coefficient of determination test. Testing this research using computer software, namely SPSS Version 25. The results of this study indicate that product quality and price perception variables have a partial effect on consumer satisfaction with SomeThinc products. In addition, the variables of product quality and price perception have a simultaneous effect on consumer satisfaction with SomeThinc's products.